2007
DOI: 10.1016/j.msea.2007.03.063
|View full text |Cite
|
Sign up to set email alerts
|

Fe2O3/aluminum thermite reaction intermediate and final products characterization

Abstract: Radial combustion experiments on Fe 2 O 3 /aluminum thermite thin circular samples were conducted. A stoichiometric (Fe 2 O 3 + 2Al) and four over aluminized mixtures were tested. The combustion products were characterized by X-ray diffraction and Mössbauer spectroscopy and the influence of Fe 2 O 3 /aluminum ratio on their composition was assessed. The main products were identified as alumina (␣-Al 2 O 3 ) and iron (Fe). A significant amount of hercynite (FeAl 2 O 4 ) was detected, decreasing with the aluminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(61 citation statements)
references
References 35 publications
3
51
0
1
Order By: Relevance
“…1 and Table 1). Chemical and physical characterisation of reactants, and mixtures preparation procedure were presented in previous papers (Durães et al, 2006a(Durães et al, , 2006b). Reactant mixtures were compressed in a stainless steel circular box with an inner PMMA lid (vd.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 and Table 1). Chemical and physical characterisation of reactants, and mixtures preparation procedure were presented in previous papers (Durães et al, 2006a(Durães et al, , 2006b). Reactant mixtures were compressed in a stainless steel circular box with an inner PMMA lid (vd.…”
Section: Methodsmentioning
confidence: 99%
“…The obtained radial combustion propagation profiles, rates and temperatures were discussed in Durães et al (2006a). Finally, the mixtures combustion products were collected and characterized by X-ray diffraction and Mössbauer spectroscopy (Durães et al, 2006b). …”
Section: Methodsmentioning
confidence: 99%
“…Fan et al [28]reported that the value of E a by Starink method was 145 kJ/mol for the thermite reaction. Bulian et al [31].found the nearest value of 247.76 kJ/mol for the similar nano thermite reaction applying Ozawa method.…”
Section: Starink Methodsmentioning
confidence: 99%
“…Sarangi et al [27] investigated this system using different Al percent and studied its reaction kinetics. Duraes et al [28] studied the reaction intermediate and final product characterization of Al/Fe 2 O 3 system taking various molar ratio of both the constituents. Mei et al [29] made an interesting investigation for the kinetics and combustion mechanism of the reaction as given in Eq.…”
mentioning
confidence: 99%
“…The thermite reaction is usually initiated by a pyrotechnic device and hot ferric liquid is generated by the chemical reaction (Frolov and Pivkina, 1997;Duraes et al, 2007). The temperature of the chemical products usually reaches 2300 K and is enough to produce a rapid phase change from the solid to the gas phase.…”
Section: System Requirementsmentioning
confidence: 99%